When to Forgive - Affinito, Mona Gustafson (New Harbinger Publications, 1999)
Keywords: Forgiveness; dept.psy; faculty_collection

Preferences for and against stimuli paired with food - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1999)
Pigeons were presented with a concurrent-chains schedule in which terminal-link entries were assigned to two response keys on a percentage basis. The terminal links were fixed delays that sometimes ended with food and sometimes did not. In most conditions, 80% of the terminal links were assigned to one key, but a smaller percentage of the terminal links ended with food for this key, so the number of food reinforcers delivered by the two alternatives was equal. When the same terminal-link stimuli (orange houselights) were used for both alternatives, the pigeons showed a preference for whichever alternative delivered more frequent terminal links. When different terminal-link stimuli (green vs. red houselights) were used for the two alternatives, the pigeons showed a preference for whichever alternative delivered fewer terminal links when terminal-link durations were long, and no systematic preferences when terminal-link durations were short. This pattern of results was consistent with the predictions of Grace's (1994) contextual choice model. Preference for the alternative that delivered more frequent terminal links was usually stronger in the first few sessions of a condition than at the end of a condition, suggesting that the conditioned reinforcing effect of the additional terminal-link presentations was, in part, transitory.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/006-990-830-192-667 tex.type: [object Object]
Keywords: *Choice Behavior/ph [Physiology]; *Feeding Behavior/px [Psychology]; *Food Preferences; Animals; Behavior; Animal; Behavior; Animal/ph [Physiology]; Choice; Choice Behavior; Columbidae; Concurrent chains; Conditioned reinforcement; Conditioning (Psychology); Conditioning; Psychological; Feeding Behavior; Food Preferences; Key peck; Pigeons; Reinforcement (Psychology); Reinforcement probability; Reinforcement; Psychology; animal; animal behavior; article; conditioning; decision making; dept.psy; feeding behavior; food preference; physiology; pigeons and doves; psychological aspect; reinforcement

Compliance, noncompliance strategies, and the correlates of compliance in 5-year-old japanese and american children - Abe, Jo Ann A; Izard, Carroll E (Social Development, 1999)
The present study compared compliance, noncompliance strategies, and the correlates in 5-year old Japanese and American children were observed during three standardized laboratory procedures. Compliance, noncompliance strategies, and negative affect were coded during Toy Pick Up procedure. Maternal directiveness and mother-directed behaviors were coded during Mother-Child play and Free-play procedures, respectively. A baseline level of play was also obtained during the Free Play procedures to ensure that the children's willingness to engage in the Toy Pick Up procedure would not be confounded with their level of involvement with the toys. Consistent with predictions derived from a review of cross-cultural research on socialization practices, Japanese children showed longer latencies to begin picking up toys in response to maternal requests and were also more likely to engage in the `less skilled' noncompliance strategies of direct defiance and passive noncompliance than American children. The two groups of children did not, however, differ in their level of negative affect during the Toy Pick Up procedure. Contrary to expectations, maternal directiveness was not associated with compliance in either group of children. However, approach behavior to mother during Free Play was inversely correlated with compliance in Japanese, but not American children.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/066-397-543-896-492 tex.type: [object Object]
Keywords: Compliance; Cross-cultural; Preschool children; Self-regulation; dept.psy

A comparative study of quiet sleep, active sleep, and waking on the first 2 days of life - Carroll, D.A.; Denenberg, V.H.; Thoman, E.B. (Developmental Psychobiology, 1999)
Direct behavioral observation and motility monitoring procedures provide reliable data, and both are appropriate for sleep/wake state measurements starting immediately after birth. Using these procedures, newborn rats, rabbits, and humans were found to have a greater amount of quiet sleep on the day of birth rather than 24 hr later. Changes in active sleep and wake were inconsistent across the 2 days. The quiet sleep findings are contrary to the developmental course which increases with age. The findings are interpreted as a temporary adaptive response to the stress of the birth process.
12 citations (Crossref) [2023-10-31]
Keywords: Animalia; Animals; Animals and human infants; Animals; Newborn; Cross-species sleep; Female; Humans; Infant; Newborn; Male; Motor Activity; Newborn sleep; Oryctolagus cuniculus; Pregnancy; Rabbits; Rats; Sleep Stages; Sleep in neonates; Sleep; REM; Sleep/wake states in neonates; Species Specificity; Wakefulness; adaptive behavior; animal behavior; animal experiment; article; breathing rate; child behavior; dept.psy; human; human experiment; infant; nonhuman; normal human; rabbit; rat; sleep pattern; sleep time; sleep waking cycle; stress

A longitudinal study of emotion expression and personality relations in early development - Abe, J.A.A.; Izard, C.E. (Journal of Personality and Social Psychology, 1999)
To investigate emotion expression and personality relations, the authors coded infants' full-face and component positive and negative expressions during Episodes 4 through 8 of the strange situation procedure at age 18 months and obtained maternal ratings of the 5-factor model of personality when children were 3.5 years old. Full-face negative expression was directly related to Neuroticism and inversely related to Agreeableness and Conscientiousness. By contrast, component positive expression showed the exact opposite pattern of relations. Full-face positive expression was positively correlated with Extraversion and Openness to Experience. These findings indicate that full-face and component expressions may index different intensities of emotions. Emotion expression and personality relations were not mediated by the security of attachment continuum or the emotional reactivity dichotomy derived from the attachment subclassifications.
58 citations (Crossref) [2023-10-31]
Keywords: *Emotions; *Personality; Age Factors; Child; Preschool; Emotions; Female; Humans; Longitudinal Studies; Male; Personality; age; article; dept.ils; dept.psy; emotion; female; human; longitudinal study; male; personality; preschool child